Public toilet in Kuala Lumpur: the design layout and maintenance works / Zirwatul Isyqi Mazlan - Mazlan, Zirwatul Isyqi (Faculty of Architecture, Planning and Surveying, 2010)
Malaysia is a country that encompasses its own unique identities. Efforts have been carried out to develop and upgrade the travel and tours infrastructure in order to bestow the positive image from the foreigners and tourists and the locals as well. This is to show that Malaysia has everything best that can be offered to the industry and will suit to their each and eveiy needs and expectation. One of the alternative and ideas from the government is to upgrade the infrastructure that relates closely to this industiy especially the public toilets at places that attract tourists the most. This effort will hope to raise the image of Malaysia and the people. It is common in Malaysia to come across the main issue of the public toilets which is the low level of cleanliness and poor uncomfortable condition. The objective of this study is to recognize the characteristic of clean toilets, to identify the right and effective procedure of maintaining public toilets. Design aspect and its characteristic is also should be considered to ensure the ease of maintenance and suitable for users of all ages especially the disabled. From the study carried out, the result shows that public in general prefers to use the conventional public toilet due to its high privacy condition. Meanwhile, the characteristic of the Automatic Street Unit is more potential to be developed as its general condition is clean and satisfying. This is because the maintenance procedure being implemented to this unit is different from the usual procedure for the conventional public toilet. In conclusion, the cooperation from everybody is truly appreciated to achieve the government’s vision and mission in providing a better toilet facility in our countiy especially in Kuala Lumpur.